Serum erythropoietin: a useful biomarker for coronary collateral development and potential target for therapeutic angiogenesis among the patients with coronary chronic total occlusion. (June 2013) - Xu, Weixian; Guo, Zhiguo; Mi, Lin; Wang, Guisong
Abstract The study was to investigate the association of endogenous erythropoietin (EPO) and coronary collateral development. Forty-nine patients (31 with chronic total occlusion (CTO), 18 with normal coronary artery) were consecutively enrolled. The serum EPO was positively related with Rentrop class. Increased serum EPO was one of the independent predictors of good collateral development (odds ratio 1.31; p = 0.025). A significantly positive correlation was seen between serum EPO and vascular endothelial growth factor (VEGF) levels (r = 0.96, p < 0.001). Circulatory EPO may be a useful biomarker for coronary collateral development and potential target for therapeutic angiogenesis in patients with CTO.